City Know-How. Issue 2 (30th November 2018) - Grant, Marcus; McCunn, Lindsay; Anand, Sonia S.; Arora, Rishi; Booth, Gillian; Brook, Jeff; Collins, Patricia; Corsi, Daniel; de Souza, R. J.; Desai, Dipika; Gauvin, Lise; Judd, Bruce; et al.
CITY KNOW-HOW: Human health and planetary health are influenced by city lifestyles, city leadership, and city development. For both, worrying trends are leading to increasing concern and it is imperative that human health and environmental impacts become core foci in urban policy. Changing trajectory will require concerted action; the journal Cities & Health is dedicated to supporting the flow of knowledge, in all directions, to help make this happen. We wish to foster communication between researchers, practitioners, policy-makers, communities, and decision-makers in cities. This is the purpose of the City Know-how section of the journal. 'Research for city practice' disseminates lessons from research by explaining key messages for city leaders, communities, and the professions involved in city policy and practice. 'City shorts' provide glimpses of what is being attempted or achieved 'on the ground' and 'case studies' are where you will find evaluations of interventions. Last, 'Commentary and debate' extends conversations we are having to develop and mobilize much needed new thinking. Join in these conversations. In order to strengthen the community of interest, we would like to include many and varied voices, including those from younger practitioners and researchers who are supporting health and health equity in everyday urban lives.